Early detection of trichinella spiralis in muscle of infected mice by real-time fluorescence resonance energy transfer PCR - Tantrawatpan C. (2014)
Real-time fluorescence resonance energy transfer (FRET) PCR and melting curve analysis using newly developed fluorophore-labeled hybridization probes were applied for the detection of Trichinella spiralis DNA in muscle of mice following oral inoculation with 300 T. spiralis larvae. The developed assay could detect and differentiate T. spiralis, Trichinella papuae, and Trichinella pseudospiralis DNAs by the different melting temperatures (Tm). The assay had a detection limit of 5×102 positive control plasmid copies, which was equivalent to 1 ng of T. spiralis DNA spiked into 250 mg of muscle sample. No fluorescence signal was detected when the technique was applied to the DNA of 27 parasites other than Trichinella spp. The assay could detect T. spiralis DNA in muscle at 7, 14, and 21 days postinoculation. The range, mean±standard deviation, and median of the Tm values of all positive muscle tissue samples were 60.4-60.8, 60.6±0.2, and 60.5, respectively. This assay provides an effective tool for the specific, sensitive, and high-throughput detection of T. spiralis DNA in muscle during the early stage of infection. In addition, the technique can be useful for epidemiologic surveillance in naturally infected wildlife. © Copyright 2013, Mary Ann Liebert, Inc. 2013.